Gary Larson and the Far Side - Soper, Kerry (Great comics artists., 2018)
Kerry D. Soper reminds us of The Far Side's groundbreaking qualities and cultural significance in Gary Larson and "The Far Side." In the 1980s, Gary Larson (b. 1950) shook up a staid comics page by introducing a set of aesthetic devices, comedic tones, and philosophical frames that challenged and delighted many readers, even while upsetting and confusing others. His irreverent, single panels served as an alternative reality to the tame comedy of the "family-friendly" newspaper comics page, as well as the pervasive, button-down consumerism and conformity of the Reagan era. In this first full study of Larson's art, Soper follows the arc of the cartoonist's life and career, describing the aesthetic and comedic qualities of his work, probing the business-side of his success, and exploring how The Far Side brand as a whole--with its iconic characters and accompanying set of comedic and philosophical frames--connected with its core readers.